Manufacturing of composites - Loos, A. C.; Hyer, M. W. (American Society for Composites series on advances in composite materials, 2013)
"Book comprises 16 original papers on the processing and manufacturing of thermoset and thermoplastic composites. Nine chapters cover modeling and process parameters for many shapes of thermosets using RTM, VARTM and CRTM. Five chapters focus on thermoplastics, including FEM analysis, preforms, and optimizing manufacturing. The book concludes with important chapters on new processes, such as vacuum-bag-only prepregs (VBO) for out-of-autoclave (OOA) fabrication of aerospace composites."--Publisher description